DEGRADASI LIMBAH TEKSTIL MENGGUNAKAN JAMUR LAPUK PUTIH Daedaleopsis eff. confragosa - Dinatha, Ngurah Mahendra (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract The objectives of this research are to determine the optimum conditions (pH, concentration of fungi, and incubation period) of degradation of textile dyeing waste using Daedaleopsis eff. confragosa and to determine the quality of the processed waste based on the parameters of chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS), pH, and its color. The fungi was collected from a plantation areal in Negara, Bali and the untreated waste itself was also collected from a home textile dyeing industry in Negara, Bali. After rejuvenation process of the fungi, the optimum conditions were obtained by collecting the COD data at various pH (4 - 10) and concentration of fungi (3% - 9%).We found that the degradation will be optimally progressing at pH 4 and fungi concentration of 6%. Finally, the optimum period of degradation was determined by varying the incubation day from 0 - 12 days at optimum conditions. The optimum incubation period was 9 days. The treatment of the dyeing waste with fungi can decrease the level of the color, TSS, COD and BOD5 up to 81.05%, 70.21%, 85.17%, and 74.09% respectively.
Keywords: Keyword: Daedaleopsis eff. confragosa, textile waste, degradation, optimum condition.